Sociophonetic Markers of Social Mobility in George Bernard Shaw's Pygmalion - Dien Achmad Yusril Izza; Siti Aisyah; Yuliyanto Sabat (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Language operates not only as a communicative tool but also as a marker of class and a gateway to social mobility. This study examines how phonetic change and idiolectal shift function as determinants of social mobility in George Bernard Shaw's Pygmalion. Using a qualitative textual analysis design, the play is read through sociophonetic theory integrated with sociological criticism, Marxist literary criticism, and Bourdieu's notion of linguistic capital. Data were drawn from dialogues, phonetic spellings, and character interactions that reveal pronunciation change, idiolectal development, and class relations, then interpreted in three stages: identification, interpretation, and synthesis. The analysis shows that Shaw represents accent as a decisive marker of class, with Eliza Doolittle's Cockney speech initially fixing her working class position and shaping others' perceptions of her. Through Higgins's phonetic training, Eliza acquires not only a prestigious accent but a broader idiolectal shift in vocabulary, communicative style, and confidence, functioning as linguistic capital that grants her temporary access to elite society. However, language alone cannot dissolve structural inequality: Eliza continues to face uncertainty about identity, independence, and full social acceptance. Pygmalion thus portrays language as both an instrument of empowerment and a mechanism that reproduces class hierarchy.